OPTIMASI PROSES DIFUSI UAP PADA DAUN SEREH DAPUR - Zuhdi Ma'sum; Wahyu Diah Proborini (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2017)
This study aims to produce a model of household scale industries which are used in urban areas to pay attention to the efficient use of water resources, energy and land. Results of essential oils stored to determine the stability of the composition of the product citral essential oils are processed using steam distillation. Industrial model made from raw material supply of land is limited, the process is effective and efficient use of water and energy to economic analysis. The raw material used is the lemongrass or commonly called Lemongrass kitchen. Kitchen lemongrass plant is observed from planting to harvest right. The area required to sustain the process of production. Methods of planting lemongrass kitchen done naturally without any special treatment such as fertilization and pest control. Tools and processes developed is steam distillation. Engineering tools in order to get the process done the shortest and the least use of energy. A short process to obtain due to optimum cooling rate. Optimum cooling will reduce the processing time and minimize water usage. From the results of research in getting to the land area is 4 x 6m2 can generate lemongrass leaves the kitchen as much as 40kg. Essential oils are produced ± 120ml per day in 4 times long process with total process time 12h. The use of fuel by 12kg LPG per day with a volume of water use remain. With this process, this study managed to shorten the process that the effect of reducing energy and minimize water usage. The advantage that can be gained per day ± Rp310.000. In storage until 23bulan, citral percentage did not change with the level of 28% - 45%.